In vitro and in vivo evaluation of electrospun cellulose acetate/gelatin/hydroxyapatite nanocomposite mats for wound dressing applications. (31st October 2018) - Samadian, Hadi; Salehi, Majid; Farzamfar, Saeed; Vaez, Ahmad; Ehterami, Arian; Sahrapeyma, Hamed; Goodarzi, Arash; Ghorbani, Sadegh
Abstract: The present study aimed to evaluate the efficacy of cellulose acetate/gelatin/nanohydroxyapatite (CA/Gel/nHA) nanocomposite mats as the wound dressing. The dressings were prepared with electrospinning of CA/Gel solutions containing 12.5, 25 and 50 mg nHA. The dressings were evaluated regarding their water uptake capacity, morphology, tensile strength, water vapour transmission rate, wettability and cellular response with L929 cell line. The results showed that the concentration of nHA had a direct correlation with porosity, water contact angle, water uptake, water vapor transmission rate and proliferation. In vivo studies showed that all dressings had higher wound closure percent than the sterile gauze, as the control. The highest wound closure value was achieved in the CA/Gel +25 mg nHA group, which showed 93.5 ± 1.6%. The histological and the histomorphometric examinations of the wounds revealed that the CA/Gel +25 mg nHA dressing had the greatest collagen synthesis, re-epithelialization, neovascularization and also the best cosmetic appearance. Based on our finding, it could be concluded the applicability of electrospun nanofibrous CA/Gel/nHA dressings for successful wound treatment.